Answer:
C. Is you answer
Step-by-step explanation:
What you have to do is you take the second equation and plug it into the y of the first equation to get
-2x^2+-3x^2+5=-5. You will then add the -2x^2 and the -3x^2 together to get
-5x^2+5=-5. You will then minus the 5 from both sides to get
-5x^2=-10. You will then divide the -5 from both sides to get
x^2=2. You will then square root it to get
x=sqrt2 and -sqrt2.
You will then plug the sqrt2 into the second equation into the x like this
y=-3(sqrt2)^2+5. and you answer wil be -1.
So C is your answer.